Candidature file of the Mevlevi Sema Ceremony : known historically as the Mevlevi Âyîn-i Şerîf or Sema Mukabele-i Şerîf the Mevlevi sacred rituals or sacred encounter of whirling for UNESCO’s proclamation of “masterpieces of the oral and intangible heritage of humanity (Ankara)
5, 128, yak. 20, 20 y.